2005
DOI: 10.1152/ajprenal.00308.2004
|View full text |Cite
|
Sign up to set email alerts
|

The role of NOS2 and NOS3 in renal protein and arginine metabolism during early endotoxemia in mice

Abstract: Luiking, Yvette C., Marcella M. Hallemeesch, Wouter H. Lamers, and Nicolaas E. P. Deutz. The role of NOS2 and NOS3 in renal protein and arginine metabolism during early endotoxemia in mice. ⅐ min Ϫ1 in WT) (P Ͻ 0.05), and de novo arginine production was lower in NOS2 Ϫ/Ϫ mice. After LPS challenge, renal protein turnover and arginine production increased in all three groups (P Ͻ 0.05), even though renal de novo arginine synthesis did not increase. The expected increase in renal citrulline production and disposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Unlike WT mice, NOS3 Ϫ/Ϫ mice did not increase citrulline production (production even decreased in NOS3 Ϫ/Ϫ mice). This seems in line with the observation that these mice did not increase plasma arterial citrulline after LPS (30).…”
Section: Role Of Nos2 and Nos3 In Endotoxemiasupporting
confidence: 92%
See 3 more Smart Citations
“…Unlike WT mice, NOS3 Ϫ/Ϫ mice did not increase citrulline production (production even decreased in NOS3 Ϫ/Ϫ mice). This seems in line with the observation that these mice did not increase plasma arterial citrulline after LPS (30).…”
Section: Role Of Nos2 and Nos3 In Endotoxemiasupporting
confidence: 92%
“…In these mice, arterial plasma citrulline increased from 70 to 90 mM after LPS (30). Unlike WT mice, NOS3 Ϫ/Ϫ mice did not increase citrulline production (production even decreased in NOS3 Ϫ/Ϫ mice).…”
Section: Role Of Nos2 and Nos3 In Endotoxemiamentioning
confidence: 82%
See 2 more Smart Citations
“…1,2,21) Partial inhibition of NOS activity may have beneficial effects on alleviating arginine deficiency and inhibiting excess NO-induced complications in inflammation. 6,7,14) However, both animal and human studies have shown inconsistent results on the therapeutic effects of NOS inhibitors.…”
Section: Discussionmentioning
confidence: 99%